Implementasi Metode AHP Pada Sistem Pendukung Keputusan Wisata Taman Kota Medanw - Pebrianti, Lidia; Sirait, Gian Patar P.; Purba, Yeremia Tiopan Pandapotan (UNIB Press, 2022)
Parks are the most alternative tourist attractions. With an open area, as well as a lot of various plants, it really supports the general public just to relax with the family. When traveling, tourists usually decide to visit interesting tourist destinations. The number of tourist destinations available, often makes tourists confused about choosing a destination according to their preferences. Therefore, this research is intended for tourists to be able to determine park tourism destinations in Medan based on several categories based on beauty, security, and facilities. One of the computational methods intended to assist in current decision making is a decision support system or Analytic Hierarchy Process (AHP). In a decision support system, any information can be processed into the best alternatives as an alternative decision result. From the results of the questionnaire analysis stage, 20 out of 31 respondents had difficulty in choosing a park tourism destination. After using the AHP method, the first place is The Le Hu Garden with a weight of 0.501, the second is followed by Taman Cadika Pramuka with a weight of 0.488, and in the last order Taman Sri Deli with a weight value of 0.473.